UPAYA PEMBERDAYAAN KELOMPOK MUDA DAN IBU â€œGMIT EBENHAEZER BILAMUNâ€ TERHADAP PENERAPAN ECO FARMING MENGGUNAKAN LIMBAH TEMPURUNG LONTAR SEBAGAI BIOCHAR - Merpiseldin Nitsae; Jonathan Ebet Koehuan; Hildegardis Missa; Hartini Realista Lydia Solle; Erik Sandy Banu; Arniati Ina Kii; Patrisia Marfiana Dae Lolonrian (Jurnal Abdi Insani, 2023)
Community Partnership Empowerment (PKM) activities have been carried out in the youth group and Mrs. GMIT Ebenhaezer Bilamun, Kupang Regency, East Nusa Tengara Province.The youth group in the church organization system is known as the backbone of the church while the mothers' group is known as the family kitchen. The number of people in this congregation is 105 households. Therefore, empowerment efforts in the agricultural sector for young people and mothers need to be carried out to improve the welfare of the congregation or community, especially families.The aim of this activity is to introduce, provide understanding, and knowledge an environmentally friendly agricultural system (eco farming) through the use of palm oil shells into biochar in the church environment. The methods of activities carried out are counseling (socialization), training and mentoring (plot demonstration using an intercropping system for land measuring 300 m2). Socialization regarding eco farming, intercropping systems, and bokashi. Training on making biochar using palmyra shells called â€œCharTaâ€. Assistance is carried out by demonstrating plots of the intercropping system for mustard greens, kale, celery, long beans, spinach and pumpkin. Mentoring activities will continue until December 2023. After this PKM activity, it shows that the knowledge and skills of the young group and Mrs. GMIT Ebenhaezer Bilamun have increased regarding the implementation of the eco farming system in the church environment using â€œCharTaâ€ (the name of the biochar product which has been protected according to Copyright No. EC202380592 dated 13 September 2023). The level of knowledge and skills that increased was the understanding of biochar (52.94% to 82.35%); eco farming system and intercropping planting system (41.18% to 100%); and land utilisation and farmer groups (52.94% to 100%). The results of the assistance will be obtained until this activity is completed in December 2023.